2022
DOI: 10.3389/fpsyg.2022.987537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on sleep quality of college students: Chain intermediary effect of mindfulness and ruminative thinking

Abstract: The Physical Exercise Rating Scale, Mindfulness Attention Awareness Scale (MAAS), Ruminative Thinking Scale (RRS), and Pittsburgh Sleep Quality Index (PSQI) are used to conduct the questionnaire among a sample of 1,006 college students (average age = 19.95 years, SD = 1.86 years) to figure out whether there is any correlation between physical exercise and sleep quality in college students as well as how the mechanism of mindfulness and ruminative thinking plays a role in them. For data analysis, the Harman sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 65 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have discussed and confirmed the positive effects of physical exercise on the mental health of primary and middle school students or college students (e.g., Song et al, 2022;Ye et al, 2022). Thus, scholars believe that physical exercise can promote the growth of left-behind children, but lack empirical evidence to support this claim.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed and confirmed the positive effects of physical exercise on the mental health of primary and middle school students or college students (e.g., Song et al, 2022;Ye et al, 2022). Thus, scholars believe that physical exercise can promote the growth of left-behind children, but lack empirical evidence to support this claim.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologically, physical exercise eliminates or reduces psychological distress such as anxiety and nervousness, effectively suppresses excessive arousal, and achieves improved sleep (43). It has been established that physical exercise can increase the level of positive thoughts, inhibit ruminative thinking, and improve sleep quality in individuals (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality problems were measured using the Chinese version of Pittsburgh Sleep Quality Index scale (PSQI; Liu et al, 1996 ), which has good validity, internal consistency and test–retest reliability, and been widely used among Chinese adolescents (e.g., Deng et al, 2021 ; Wang W. et al, 2022 ; Ye et al, 2022 ). The PSQI comprises 18 self-rated items, including seven factors: subjective sleep quality, time to sleep, sleep duration, sleep efficiency, sleep disturbance, hypnotic medication, and daytime function.…”
Section: Methodsmentioning
confidence: 99%